Prevalence of red cell alloantibodies in transfusion-dependent thalassemia: a cross-sectional study from Bangladesh - Joarder, Nirjharini; Afrida, Nudrat; Rahman, Mujahida; Harun, Maha; Sultana, Wahida; Hossain, Shohag; Reza, Nayon (International Journal of Research in Medical Sciences, 2026)
Background: Red cell alloimmunization is a significant transfusion complication in transfusion-dependent thalassemia (TDT) patients, complicating subsequent transfusions and hematopoietic stem cell transplantation (HSCT). The aim of the study was to determine the prevalence of red cell alloimmunization among TDT patients seen at a specialized center in Bangladesh, define the spectrum of clinically significant alloantibodies, and identify risk factors with special reference to transplant-eligible patients. Methods: This was a cross-sectional study conducted at Islamic Bank Hospital and Cardiac Centre, Dhaka, Bangladesh from February 2023 to April 2024, among 860 transfusion-dependent thalassemia patients. A three-cell screening panel was used to screen red cell antibodies in all the samples. Screen-positive samples were detected by a fourteen-cell identification panel on a fully automated immunohematology analyzer. Clinical and laboratory data, including hemoglobin, serum ferritin, age, sex, and thalassemia subtype, were collected. Modified Poisson regression with robust standard errors was employed to determine risk factors. Results: Total red cell alloimmunization prevalence was 9.8% (95% CI: 8.0-11.9%), and all of the detected antibodies were clinically significant. Of alloimmunized patients, 45.2% were ≤16 years (transplant-eligible age). The most frequent were anti-E (33.3%), anti-c (21.4%), anti-D (16.7%), and anti-C (11.9%) from the Rh system, and anti-Kpa (9.5%) and anti-Kpb (7.1%) from the Kell system. Risk factors were age ≥16 years (aPR 1.68, 95% CI: 1.13-2.52) and β-thalassemia major subtype compared with HbE/β-thalassemia (aPR 0.31, 95% CI: 0.20-0.47). Conclusions: Red cell alloimmunization occurs in nearly 10% of TDT patients in Bangladesh and has significant implications for transplant-eligible patients. Extended phenotyping and prophylactic matching practices need to be implemented, particularly among high-risk groups, to optimise transfusion management and transplant readiness.